Determinant Analysis Of Capital Adequacy Ratio In Indonesian Sharia Bank - PRAKOSO, ANANDIKA TEGUH (Jurnal Ilmiah Mahasiswa FEB, 2019)
This study aims to determine the influence of bank performance variables onthe Capital Adequacy Ratio in Indonesian Sharia Banks for 2016-2018. Datasampling is gathered by utilizing purposive sampling with the criteria ofIndonesian sharia commercial banks presenting financial statements for themonthly period from 2016 to 2018. There are 3 Categories of ShariaCommercial Banks in Indonesia consisting of BUKU 1, BUKU 2, BUKU 3 from2016 to 2018. Data is obtained from Bank Indonesia Published FinancialReports by applying panel data regression analysis and estimation model ofRandom Effect Model (REM) with the help of computer of Stata version 13, asthe primary software to process the research data. The results of the analysisindicate that ROA, NPF, FDR, Short-term Mismatch have a significant effect onCAR with different levels of significance.Keywords: Capital Adequacy Ratio, bank performance, Islamic commercial banks.